2015
DOI: 10.1128/microbiolspec.mb-0001-2014
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Development

Abstract: During the past decade we have gained much knowledge about the molecular mechanisms that are involved in initiation and termination of biofilm formation. In many bacteria, these processes appear to occur in response to specific environmental cues and result in, respectively, induction or termination of biofilm matrix production via the second messenger molecule c-di-GMP. In between initiation and termination of biofilm formation we have defined specific biofilm stages, but the currently available evidence sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
110
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(126 citation statements)
references
References 93 publications
1
110
0
1
Order By: Relevance
“…strain MR-S7 (Kusada et al, 2014). The importance of QS for the biofilm formation could be due to secretion of important compounds like extracellular DNA, the biosurfactant rhamnolipid and the secretion of the BapA-protein as shown in P. aeruginosa (Tolker-Nielsen, 2015). Furthermore, QS-compounds play an important role in P. fluorescence 2p24 for its colonization on wheat roots and development of biocontrol ability toward the take-all disease fungus (Wei and Zhang, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…strain MR-S7 (Kusada et al, 2014). The importance of QS for the biofilm formation could be due to secretion of important compounds like extracellular DNA, the biosurfactant rhamnolipid and the secretion of the BapA-protein as shown in P. aeruginosa (Tolker-Nielsen, 2015). Furthermore, QS-compounds play an important role in P. fluorescence 2p24 for its colonization on wheat roots and development of biocontrol ability toward the take-all disease fungus (Wei and Zhang, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…1). For example, there are a variety of bacterial structures such as adhesins, type IV pili, and lipopolysaccharide (LPS) that are involved in attachment, and these bacterial structures are specifically regulated by environmental cues [9,34]. Recent studies demonstrated that the initiation of biofilm formation occurs with an increase in c-di-GMP, an intracellular second messenger [35][36][37][38][39].…”
Section: Attachment Of P Aeruginosa Biofilmsmentioning
confidence: 99%
“…In natural environments, microorganisms form complex multicellular surface-associated communities known as biofilms. The first step of biofilm formation is the reversible attachment of single cells to the surface (Goller and Romeo, 2008;Tolker-Nielsen, 2015;Berne et al, 2018). For most bacteria, the initial attachment step requires flagellar motility and pili.…”
Section: Introductionmentioning
confidence: 99%